Beliefs of Capitalism in the System of Knowledge of the Soviet Pupil - N. K. Gurkina (Управленческое консультирование)
In ideological installations and school practices of the Soviet education system one of the major concepts was “capitalism” — ideology, a social and economic structure, “the world project”, antagonistic to socialist. In the article is considered as developed in 20th and 30th and what place was taken by ideas of capitalism in the system of knowledge of the Soviet pupils, in their ideological and political education. The role of these representations in formation of outlook of the pre-war pupils is investigated.